Weighted Graphs - Erciyes, K (Guide to Graph Algorithms, 2018)
A weighted graph can have weights associated with its edges or its vertices. The weight on an edge typically denotes the cost of traversing that edge and the weights of a vertex commonly show its capacity to perform some function. In this chapter, we review sequential, parallel, and distributed algorithms for weighted graphs for two specific tasks; the minimum spanning tree problem and the shortest path problem.